2007
DOI: 10.1007/s11630-007-0337-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational cavitation flows at inception and light stages on an axial-flow pump blade and in a cage-guided control valve

Abstract: Cavitation flows induced around an axial-flow pump blade and inside a high pressure cage-type valve are simulated by a two-dimensional unsteady Navier-Stokes analysis with the simplest treatment of bubble dynamics. The fluid is assumed as a continuum of homogeneous dispersed mixture of water and vapor nuclei. The analysis is aimed to capture transient stages with high amplitude pressure change during the birth and collapse of the bubble especially at the stage of cavitation inception. By the pump blade analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…First, how to most accurately model the geometry using an adequate mesh. Even the most recent works presented in the literature resort to simplifications applied into the computed geometry [17,18,19]. In the present case the only simplification was the non-inclusion of wear-ring seals.…”
Section: Introductionmentioning
confidence: 99%
“…First, how to most accurately model the geometry using an adequate mesh. Even the most recent works presented in the literature resort to simplifications applied into the computed geometry [17,18,19]. In the present case the only simplification was the non-inclusion of wear-ring seals.…”
Section: Introductionmentioning
confidence: 99%
“…The cavitation appears at the front of the ba e and tip of the inner and outer nozzle wall in the electro-hydraulic servo valve 4 . Saito et al 5 investigated the highpressure cover valve and concluded that the cavitation bubble rst emerges near the valve port at a small opening and collapses after a short distance. Lee et al 6 performed the numerical simulation of the reversing globe valve and established that the cavitation strength in the valve decreased with increase of the spool tail and wrist lengths.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] It is now possible to numerically study the transient dynamic characteristics of pumps, and there are many related research results. Using a twodimensional unsteady Navier-Stokes analysis with the simplest treatment of bubble dynamics, Saito et al 13 simulated the cavitation flows around an axial-flow pump blade to capture the transient stages with high amplitude pressure changes during the birth and collapse of bubbles. Zhang et al 14 simulated the three-dimensional unsteady turbulent flow in axial-flow pumps using the Navier-Stokes solver embedded with k-e RNG turbulence model and the SIMPLEC algorithm and discussed the pressure fluctuation, static pressure distribution, and axial velocity at the rotor outlet; few years later, Zhang et al 15 analyzed the transient characteristics of tip leakage vortices and the tip leakage dynamics in axial-flow pumps using LES to predict and control cavitation, noise, and vibration.…”
Section: Introductionmentioning
confidence: 99%